1964
DOI: 10.1070/pu1964v006n06abeh003613
|View full text |Cite
|
Sign up to set email alerts
|

Fifth All-Union Conference on the Theory of Semiconductors

Abstract: Trapping and Hall mobility data have been obtained for samples of Ge doped with Pt and compensated with Sb which suggest that the charge state of the empty 0.2 ev Pt level is triply negative. The thermal electron capture rates are (1.8 i: 0.6) x lo-' cm3 s -' at 77°K and (6 2) x lo-'' cm3 s-' at 2 6 . 2 "~. These rates are much higher than for the 0.2 ev Aucentre. The maximum high-to-low field capture rate ratios were 8.4 and 315 respectively and negative resistance phenomena were observed at both temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Polaritons, bosonic quasiparticles resulting from the coupling between electromagnetic radiation and dipole-carrying excitations, were first conceived by Tolpygo in 1950 [1] and observed by Hopfield in 1958 [2], at the time used as a term for quantization of the polarization field created upon interaction between photons and electron-hole pairs (excitons). While the broader definition allows for many types of polaritons named for various light-dipole pairings, including intersubband-polaritons (coupling of light to intersubband electronic levels) [3], phonon-polaritons (coupling of light to optical phonons), [4][5][6] and Braggpolaritons (coupling of Bragg modes to excitons) [7,8], here we will focus largely on the aforementioned exciton-polaritons and interactions between light and surface plasmons known as surface-plasmon polaritons (For an excellent review of exciton-polariton coupling in semiconductors, see [9].…”
Section: Exciton-polaritonsmentioning
confidence: 99%
“…Polaritons, bosonic quasiparticles resulting from the coupling between electromagnetic radiation and dipole-carrying excitations, were first conceived by Tolpygo in 1950 [1] and observed by Hopfield in 1958 [2], at the time used as a term for quantization of the polarization field created upon interaction between photons and electron-hole pairs (excitons). While the broader definition allows for many types of polaritons named for various light-dipole pairings, including intersubband-polaritons (coupling of light to intersubband electronic levels) [3], phonon-polaritons (coupling of light to optical phonons), [4][5][6] and Braggpolaritons (coupling of Bragg modes to excitons) [7,8], here we will focus largely on the aforementioned exciton-polaritons and interactions between light and surface plasmons known as surface-plasmon polaritons (For an excellent review of exciton-polariton coupling in semiconductors, see [9].…”
Section: Exciton-polaritonsmentioning
confidence: 99%
“…However, the procedure cannot be extended to treat higher order terms that are important for lattice dynamic calculations. Following the procedure suggested by Tolpygo [14] the Born-Oppenheimer energy is expressed as a function of dipole moments and nuclear coordinates. The details of this analysis are given by Sengupta [17].…”
Section: Calculation Of Static Dielectric Properties and Lattice Dymentioning
confidence: 99%
“…Interestingly, at sufficiently high-power levels an electromagnetic field of subgap frequency, which is of the order of a few hundred GHz for a superconductor with a T c of 5 K, may stimulate superconductivity itself. Discovered in 1966 by Wyatt et al [1] via an enhancement of the supercurrent in tin films in the Meissner state in the presence of a microwave electromagnetic field, this counterintuitive non-equilibrium effect has inspired extensive research both experimentally [2][3][4][5][6][7][8] and theoretically. [9][10][11][12] A comprehensive review can be found in Ref.…”
mentioning
confidence: 99%
“…Stimulation of superconductivity at microwave frequencies was observed in various type-I superconducting systems such as thin films, [2,3] cylinders [5] and almost all types of weak links. [4] In spatially homogeneous superconductors, the effect was explained by Eliashberg in 1970 to be a consequence of an irradiation-induced redistribution of quasiparticles away from the gap edge.…”
mentioning
confidence: 99%